2021
DOI: 10.1007/s12640-021-00402-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Anti-high Mobility Group Box-1 Monoclonal Antibody Against Methamphetamine-Induced Dopaminergic Neurotoxicity

Abstract: High mobility group box-1 (HMGB1) is a ubiquitous non-histone nuclear protein that plays a key role as a transcriptional activator, with its extracellular release provoking inflammation.Inflammatory responses are essential in methamphetamine (METH)-induced acute dopaminergic neurotoxicity. In the present study, we examined the effects of neutralizing anti-HMGB1 monoclonal antibody (mAb) on METH-induced dopaminergic neurotoxicity in mice. BALB/c mice received a single intravenous administration of anti-HMGB1 mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…In contrast, Frank et al showed that the hazard-related molecular pattern HMGB1 mediates the neuroinflammatory effects of methamphetamine use [180]. Other studies also show that methamphetamine injection induces hyperthermia, an increase in plasma HMGB1 concentration, the degeneration of dopaminergic nerve endings, microglia accumulation and the extracellular release of neuronal HMGB1 in the striatum [181]. The results of a meta-analysis that showed that methamphetamine exposure increases beta-amyloid precursor protein expression through an HMGB1-related pathway in Alzheimer's disease patients appear to be interesting [182].…”
Section: Hmgb1 and Use Of Psychoactive Substancesmentioning
confidence: 98%
“…In contrast, Frank et al showed that the hazard-related molecular pattern HMGB1 mediates the neuroinflammatory effects of methamphetamine use [180]. Other studies also show that methamphetamine injection induces hyperthermia, an increase in plasma HMGB1 concentration, the degeneration of dopaminergic nerve endings, microglia accumulation and the extracellular release of neuronal HMGB1 in the striatum [181]. The results of a meta-analysis that showed that methamphetamine exposure increases beta-amyloid precursor protein expression through an HMGB1-related pathway in Alzheimer's disease patients appear to be interesting [182].…”
Section: Hmgb1 and Use Of Psychoactive Substancesmentioning
confidence: 98%
“…Amphetamines also alter the microglia number and morphology. It has been shown that these cells can exhibit increased soma size and thicker processes after METH exposure in the striatum [ 155 , 204 - 207 ], hippocampus [ 147 , 208 ], thalamus, dorsal raphe/central gray area, inferior colliculus [ 208 ], somatosensory and piriform cortices, periaqueductal gray [ 209 ] and substantia nigra pars compacta [ 210 ]. On the other hand, the total dendritic length and the cell soma area in the hilus were not different after the reinstatement of METH self-administration [ 211 ].…”
Section: Responses Of Microglia To Psychostimulantsmentioning
confidence: 99%
“…The HMGB1 protein expresses 99% identity among mammals, which should facilitate the process, while on the other hand molecules attached to the extracellular HMGB1 complicate the development of HMGB1-binding antagonists, especially when HMGB1-RAGE endocytosis needs to be targeted. One academic research group in Japan has generated an anti-HMGB1 mAb recognizing the repetitive C-terminal part of the molecule, which conceivably might be an element less engaged by partner molecules in vivo [ 89 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 ]. This antibody has exhibited impressive therapeutic efficacy in many animal models of neuroinflammation both in the central nervous system and in the periphery, most of which events are TLR4-dependent.…”
Section: Key Challenges In the Hmgb1 Fieldmentioning
confidence: 99%